Does Organizational Justice Moderate The Negative Influence of Job Insecurity on Organizational Commitment? - Anik Herminingsih (Sekolah Tinggi Manajemen IPMI, 2021)
The increasing use of contract labor has triggered job insecurity resulting in a decline in organizational commitment. It is a challenge for the management of human resources to keep the committed employees by providing good treatments, for example, by giving a sense of justice of the organization. The study aims to analyze whether organizational justice moderates the negative influence of job insecurity on organizational employee commitment. The study involves 30 students of regular2; the data are obtained by filling in a self-rating questionnaire. The data are analyzed by using hierarchical regression model by using SPSS. The results show that job insecurity affects negatively and significantly on organizational employee commitment, while organizational justice affects positively and significantly on organizational employee commitment. Organizational justice has not been proven to moderate the influence of job insecurity on organizational employee commitment. Keywords: moderation, negative influences, organisasional commitment, insecurity